Brain and soccer: Functional patterns of brain activity during the generation of creative moves in real soccer decision‐making situations. Issue 3 (26th September 2018) - Fink, Andreas; Bay, Jürgen U.; Koschutnig, Karl; Prettenthaler, Katharina; Rominger, Christian; Benedek, Mathias; Papousek, Ilona; Weiss, Elisabeth M.; Seidel, Anna; Memmert, Daniel
Abstract: This fMRI study investigated brain activity while soccer players were imagining creative moves in real soccer decision‐making situations. After presenting brief video clips of a soccer scene, participants had to imagine themselves as the acting player and think either of a creative or obvious move that might lead to a goal. Findings revealed stronger activation during trials in which the generation of obvious moves was required, relative to trials requiring creative moves. The reversed contrast (creative > obvious) showed no significant effects. Activations were mainly left‐lateralized, primarily involving the cuneus, middle temporal gyrus, and the rolandic operculum, which are known to support the processing of multimodal input from different sensory, motor and perceptual sources. Interestingly, more creative solutions in the soccer task were associated with smaller contrast values for the activation difference between obvious and creative trials, or even with more activation in the latter. Furthermore, higher trait creative potential (as assessed by a figural creativity test) was associated with stronger activation differences between both conditions. These findings suggest that with increasing soccer‐specific creative task performance, the processing of the manifold information provided by the soccer scenario becomes increasingly important, while in individuals with higher trait creative potential these processes were recruited to a minor degree. This study showed that soccer‐specific creativity tasks modulate activation levels in a network of regions supporting various cognitive functions such as semantic information processing, visual and motor imagery, and the processing and integration of sensorimotor and somatosensory information.